Use of coconut cake (Cocos nucifera) in the productive performance of guinea pigs (Cavia porcellus) during the growth and fattening phases - Tantahuillca-Landeo, Folke Claudio (2025)
The study aimed to evaluate the effect of four levels of coconut cake inclusion (0, 10, 20, 30%) in the diet of guinea pigs on productive parameters during the growth and fattening phases. Four hundred male guinea pigs from the Peru genetic line were used, with an average age of 14 ± 3 days and an initial weight of 294.8 ± 4.0 g. The animals were randomly distributed into four experimental groups, each with five replicates of 20 guinea pigs, for 56 days. Key indicators such as daily weight gain (DWG), final weight (FW), feed consumption (FC), feed conversion ratio (FCR), carcass yield (CY), and economic return were recorded. No significant differences were found in the production parameters analysed (p>0.05), with average values for DWG, FW, FC, FCR, and CY between 12.6 and 13.0 g/day, 995.1 and 1020.8 g, 2161.4 and 2471.2 g/guinea pig, 3.02 and 3.49, and 73.06 and 73.64%, respectively. However, the economic analysis revealed that the treatment with 30% coconut cake presented a better profitability index. In conclusion, although the inclusion of coconut cake did not show a better animal response, it proved to be advantageous from an economic perspective.